UKRAINIAN MUSICAL FOLKLORE AS A MEANS EMOTIONAL EDUCATION OF STUDENTS JUNIOR CLASSES - I.V. Mohiley (Academy of Cognitive and Natural Sciences, 2022)
In the article it is distinguished the active forms of work with the material of Ukrainian musical folklore; which promote the education process possibilities with decision of the problem in emotional education of junior pupils.